(untitled) (Experimental biology, 2021)
There are a lot of plants with general medicinal properties in Kazakhstan. including Artemisia species, which, due to their medicinal and pharmacological properties, occupy an important place among many medicinal plants in Kazakhstan. In this study, a quantitative and qualitative analysis of the aerial part of Artemisia frigida Willd (ice wormwood), collected from the big Shymbulak river near the Dzungarian mountain in Kazakhstan. where was carried out. As a result, twenty amino acids were identified using gas-liquid chromatography.